Evaluation of the Implementation of ISO 31000-Based Risk Management in Palembang's Local Food’s MSME - Varian, Alvin Edra; Hartanti, Dwi (E-Jurnal Akuntansi; Vol 35 No 5 (2025), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia's economy but face operational and financial risks. Effective risk management helps MSMEs mitigate risks and enhance sustainability. This study evaluates the implementation of ISO 31000 risk management in MSME V, a producer of traditional Palembang food. The selection of MSME V is based on differences in sectors and locations that reflect the unique characteristics and risk challenges in each region. Using an evaluative approach, this research analyzes risk management adoption and its impact. Findings indicate that MSME V has not systematically implemented risk management, leading to instability in decision-making. This research is limited to MSME V only, which specialty Palembang food industry, without comparison with other MSMEs. Keywords: Risk Management; ISO 31000; MSME; Business Sustainability